The relationship of embedded generation modes with non-linear loads - Azizan A.W.; Ramachandaramurthy V.K.; Koon L.C. (2023)
A network voltage variation gets most severe at the generator's point of connection. This variation will be illustrated by two generation modes, namely the PQ and PV modes. This paper intends to explore the effects an embedded generation modes have on a distribution system's voltage by using PSCAD/EMTDC power simulation software on a selected Malaysian distribution network. The simulation is performed for two types of loads, namely the static load and motor load. The result shows that embedded generation in PQ mode causes excessive power that explains the rise in network bus voltage. 2011 IEEE.